Metropolitan Jewish cemeteries of the 19th and 20th centuries in Central and Eastern Europe : a comparative study - Klein, Rudolf 1955- (ICOMOS - Hefte des Deutschen Nationalkomitees, 2018)
https://www.imhof-verlag.de/metropolitan-jewish-cemeteries.html$qapplication$yInhaltsbeschreibung